Ultrasound combined with microbubble mediated immunotherapy for tumor microenvironment - Wu, Yunfeng; Li, Jiajia; Shu, Linfeng; Tian, Zhaoyu; Wu, Siru; Wu, Zuohui (Frontiers in Pharmacology, 2024)
The tumor microenvironment (TME) plays an important role in dynamically regulating the progress of cancer and influencing the therapeutic results. Targeting the tumor microenvironment is a promising cancer treatment method in recent years. The importance of tumor immune microenvironment regulation by ultrasound combined with microbubbles is now widely recognized. Ultrasound and microbubbles work together to induce antigen release of tumor cell through mechanical or thermal effects, promoting antigen presentation and T cells' recognition and killing of tumor cells, and improve tumor immunosuppression microenvironment, which will be a breakthrough in improving traditional treatment problems such as immune checkpoint blocking (ICB) and himeric antigen receptor (CAR)-T cell therapy. In order to improve the therapeutic effect and immune regulation of TME targeted tumor therapy, it is necessary to develop and optimize the application system of microbubble ultrasound for organs or diseases. Therefore, the combination of ultrasound and microbubbles in the field of TME will continue to focus on developing more effective strategies to regulate the immunosuppression mechanisms, so as to activate anti-tumor immunity and/or improve the efficacy of immune-targeted drugs, At present, the potential value of ultrasound combined with microbubbles in TME targeted therapy tumor microenvironment targeted therapy has great potential, which has been confirmed in the experimental research and application of breast cancer, colon cancer, pancreatic cancer and prostate cancer, which provides a new alternative idea for clinical tumor treatment. This article reviews the research progress of ultrasound combined with microbubbles in the treatment of tumors and their application in the tumor microenvironment.